Do I want to work from home today? Specific job crafting strategies of public service employees working from home during the COVID-19 pandemic in Germany: a qualitative study - Seinsche, Laura; Schubin, Kristina; Neumann, Jana; Pfaff, Holger (Frontiers in Psychology, 2023)
1) Background: After the outbreak of the COVID-19 pandemic employees in Europe increasingly worked from home. In the German public sector, many employees experienced working from home for the first time. Concurrently, employees could use job crafting activities to alter job demands and resources while working from home. This exploratory case study aims at shedding light on how public service employees craft their job demands and job resources, and how they perceive job satisfaction and productivity while working from home during the COVID-19 pandemic. A novel theoretical approach is applied to explore crafting activities that target specific job demands and resources when working from home, using a combined framework of resource-based job crafting based on the Job Demands-Resources model and time-spatial job crafting.(2) Methods: Qualitative telephone interviews were conducted with employees from different public sectors in Germany between December 2021 and February 2022. According to the COREQ guidelines, the 12 semi-structured interviews were audio-recorded, transcribed verbatim, and content-analyzed using MAXQDA.(3) Results: Results suggest that employees, who were new to working from home, developed personal crafting strategies for their flexible work environment. These strategies supported them to cope with hindering job demands (e. g. measures regarding work-related availability or interruptions) by optimizing their working conditions. Additionally, employees used strategies to increase their social resources (e. g. initiating meetings with colleagues) and their structural resources (e. g. installing additional work equipment, planning office and working from home days). The use of given job resources and optimization of job demands is closely linked to the time spatial demands fit. Thereby, the time spatial demands fit is used to combine work places, work hours or work tasks with the provided resources and demands in order to achieve an optimal work environment, which also facilitates employees' productivity and satisfaction.(4) Conclusions: The results enrich the resource-based and time-spatial demands job crafting research by adding specific job crafting strategies utilized by public service employees. Furthermore, the results highlight job crafting strategies for enhancing job satisfaction and productivity when working from home in the post-pandemic world, thus offering valuable insights for researchers and practitioners.